Influence of earth pressure coefficient, bedding stiffness and ground water level on shallow underground metro station - Magdum, Madan; Karkare, Bilavari (Journal of Structural Engineering, 2024)
Underground metro stations are susceptible to the significant external loads such as earth pressure, water pressure,bedding stiffness and backfill soil cover. The ground imposes formidable challenges in design due to geologicalcomplexities, ground water, induced stresses, geological formation history etc. At the initial phase of project, the designis carried based on the available limited geotechnical information. However, further analysed and modified based onthe detailed investigation. Hence, it is important to study the influence of earth pressure coefficient at rest (ko), GroundWater Level (GWL) and bedding coefficient (ks) on the design of underground metro stations to establish graphicalinteraction. The paper presents a parametric soil structure investigation for shallow cut and cover underground metrostation having soil cover of minimum 2m on roof. The wide range covers most of the geotechnical conditions acrosscities in India. 3D Finite element models are analysed considering variation in governing loads and design bendingmoments at about 20 key locations are presented graphically. The study includes wide range of 132 non-linear 3-Dfinite element structural models. The sensitivity analysis benefits for optimisation, reducing risk due to uncertaintiesand to develop the preliminary structural analysis with respect to lower bound and upper bound parameters.